A Lacanian Reading of the Two Novels The Scarlet Letter And Private Memoirs And Confessions of A Justified Sinner - Marjan Yazdanpanahi (IAIN Salatiga, 2010)
This paper discusses two novels The Private Memoirs and Confessions of a Justified Sinner and The Scarlet Letter written by James Hogg and Nathaniel Hawthorn from the perspective of Jacques Lacan theories: the mirror stage, the-name-of-the-father and desire. The mirror stage refers to historical value and an essential libidinal relationship with the body-image. The-name-of-the-father is defined as the prohibitive role of the father as the one who lays down the incest taboo in the Oedipus complex. Meanwhile, desire is neither the appetite for satisfaction, nor the demand for love, but the difference that results from the subtraction of the first from the second.Keywords: Lacanian Reading; The Mirror Stage; The-Name-Of-The-Father And Desire